2012
DOI: 10.9724/kfcs.2012.28.6.839
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics of Bread Added with Paprika Powder

Abstract: This study was carried out in order to evaluate the effects of paprika powder on bread quality. Breads were prepared with the addition of 0%, 2.5%, 5.0%, 7.5% and 10.0% of paprika powder based on wheat flour. The weight of breads with paprika powder ranged from 526.5 ∼537.3 g; that of the control was 525.0 g. The volume of the breads prepared by adding paprika powder was 1946.1∼2114.3 mL, whereas that of the control was 2144.4 mL. The height, specific volume and baking loss rate of breads with added paprika po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…The statistical analysis did not identify any significant changes in the cohesiveness of the bread crumbs based on the type of supplementation and the interactions between the variables (supplementation type and amount). Previous studies [7,34,35,38] have reported on the transformative effects adding tomato (seeds and residue) and paprika powder has on crumb texture parameters. Sogi et al [34] observed that an increase in the addition of tomato seed pomace resulted in a significant increase in wheat bread firmness.…”
Section: Texture Profile Analysis (Tpa) Of Breadmentioning
confidence: 99%
See 3 more Smart Citations
“…The statistical analysis did not identify any significant changes in the cohesiveness of the bread crumbs based on the type of supplementation and the interactions between the variables (supplementation type and amount). Previous studies [7,34,35,38] have reported on the transformative effects adding tomato (seeds and residue) and paprika powder has on crumb texture parameters. Sogi et al [34] observed that an increase in the addition of tomato seed pomace resulted in a significant increase in wheat bread firmness.…”
Section: Texture Profile Analysis (Tpa) Of Breadmentioning
confidence: 99%
“…Interestingly, Majzoobi et al [38], who used whole tomato powder for bread fortification, demonstrated that the hardness of enriched bread crumbs was lower than in their control sample, especially at higher levels of tomato powder supplementation. Choi et al [7], in their analysis of wheat bread fortified with whole pepper powder, showed that hardness, springiness, cohesiveness, and chewiness increased with the addition of paprika powder.…”
Section: Texture Profile Analysis (Tpa) Of Breadmentioning
confidence: 99%
See 2 more Smart Citations